2013
DOI: 10.1024/1010-0652/a000113
|View full text |Cite
|
Sign up to set email alerts
|

Zur Bedeutung der Intelligenz und des Fähigkeitsselbstkonzeptes bei der Vorhersage von Leistungstests und Noten in Mathematik

Abstract: Trotz der Bedeutung der Intelligenz und des Fähigkeitsselbstkonzeptes für die Schulleistung liegen nur wenige Studien zur vergleichenden Beurteilung der relativen Bedeutung der beiden Konstrukte bei der Vorhersage von standardisierten Schulleistungstests und Schulnoten vor. Ziel der vorliegenden Studie ist die Replikation einer zentralen Studie in diesem Bereich ( Helmke, 1992a ) mit verbesserten Methoden. Untersucht wurden 463 Schüler (226 weiblich) der 8. Klasse an 4 Gymnasien und 3 Realschulen. Erfasst wurd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 17 publications
2
9
0
2
Order By: Relevance
“…However, research on the relative importance of intelligence and self-concept of ability for the prediction of school achievement has produced mixed results even when researchers have included both standardized tests and school grades as indicators of performance within selected academic domains (Dresel et al, 2010; Helmke, 1992; Lau & Roeser, 2002; Lotz et al, 2018; Steinmayr & Meißner, 2013; Zaunbauer et al, 2009). With regard to students’ standardized test performance, some studies have identified intelligence as a more important predictor than students’ ability self-concept (for test performance in math and science: Helmke, 1992; Lau & Roeser, 2002; Lotz et al, 2018; Steinmayr & Meißner, 2013), as a predictor of comparable importance (for test performance in a foreign language: Zaunbauer et al, 2009), or as less important (for test performance in students’ native language: Dresel et al, 2010). With regard to school grades, some of these studies have identified students’ ability self-concept as a more powerful predictor than intelligence (for grades in native language, foreign language, and math: Dresel et al, 2010; Lotz et al, 2018; Zaunbauer et al, 2009) or as a predictor of comparable importance (for grades in math and science: Helmke, 1992; Lau & Roeser, 2002; Steinmayr & Meißner, 2013).…”
Section: The Importance Of Intelligence and Ability Self-concept For ...mentioning
confidence: 99%
See 2 more Smart Citations
“…However, research on the relative importance of intelligence and self-concept of ability for the prediction of school achievement has produced mixed results even when researchers have included both standardized tests and school grades as indicators of performance within selected academic domains (Dresel et al, 2010; Helmke, 1992; Lau & Roeser, 2002; Lotz et al, 2018; Steinmayr & Meißner, 2013; Zaunbauer et al, 2009). With regard to students’ standardized test performance, some studies have identified intelligence as a more important predictor than students’ ability self-concept (for test performance in math and science: Helmke, 1992; Lau & Roeser, 2002; Lotz et al, 2018; Steinmayr & Meißner, 2013), as a predictor of comparable importance (for test performance in a foreign language: Zaunbauer et al, 2009), or as less important (for test performance in students’ native language: Dresel et al, 2010). With regard to school grades, some of these studies have identified students’ ability self-concept as a more powerful predictor than intelligence (for grades in native language, foreign language, and math: Dresel et al, 2010; Lotz et al, 2018; Zaunbauer et al, 2009) or as a predictor of comparable importance (for grades in math and science: Helmke, 1992; Lau & Roeser, 2002; Steinmayr & Meißner, 2013).…”
Section: The Importance Of Intelligence and Ability Self-concept For ...mentioning
confidence: 99%
“…With regard to students’ standardized test performance, some studies have identified intelligence as a more important predictor than students’ ability self-concept (for test performance in math and science: Helmke, 1992; Lau & Roeser, 2002; Lotz et al, 2018; Steinmayr & Meißner, 2013), as a predictor of comparable importance (for test performance in a foreign language: Zaunbauer et al, 2009), or as less important (for test performance in students’ native language: Dresel et al, 2010). With regard to school grades, some of these studies have identified students’ ability self-concept as a more powerful predictor than intelligence (for grades in native language, foreign language, and math: Dresel et al, 2010; Lotz et al, 2018; Zaunbauer et al, 2009) or as a predictor of comparable importance (for grades in math and science: Helmke, 1992; Lau & Roeser, 2002; Steinmayr & Meißner, 2013). Not only differences between achievement indicators but also domain-specific differences may contribute to these mixed results.…”
Section: The Importance Of Intelligence and Ability Self-concept For ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Darüber hinaus ist festzustellen, dass kaum Forschungsbefunde existieren, die für die Vorhersage der Schulleistung unterschiedliche Leistungskriterien (Tests vs. Note) berücksichtigen (Steinmayr/ Meißner 2013).…”
Section: \ Theoretischer Hintergrundunclassified
“…Darüber hinaus gilt ein heterogenes Ergebnismuster zur Vorhersage von Schulleistungstests und Schulnoten durch individuelle Schülermerkmale, beispielsweise motivationale Prädiktoren, empirisch als unbestritten (Steinmayr/Meißner 2013). Bislang ist jedoch kaum geklärt wie die Prädiktoren soziokulturelle Herkunfts merkmale und elterliche motivationale Prozessbedingungen zur Vorhersage unter schiedlicher Leistungsmaße Zusammenwirken, da vorwiegend kulturelle, kommuni kative und soziale Praxen als familiale Prozessmerkmale in den Blick genommen wurden (z.…”
Section: Zusammenhänge Zwischen Strukturellen Herkunftsmerkma Len Deunclassified